PHARMA TOURISM: BUILDING A HEALTHY AND WEALTHY INDIA - Amudha R; CRESENTA SHAKILA MOTHA L; Nalini R; Alamelu R (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT The objective of the study is to know about the present scenario of pharma tourism in Indian perspective. Pharma or medical tourism, a term that also can be used to describe medical outsourcing, is characterized by travel away from one's home region to procure treatment in another. India is renowned for ancient alternative therapies such as Ayurveda, Yoga and Meditation, and Therapeutic Massage. The Indian medical tourism industry is on its way to become the most preferred destination for medical treatment for people from all around the world. The industry is expected to touch USD 6 billion by the year 2018, growing at a compounded annual rate of 20% between the years 2014 and 2018. Health care has become one of India's largest sectors - both in terms of revenue and employment. The industry comprises hospitals, medical devices, clinical trials, outsourcing, telemedicine, medical tourism, health insurance, and medical equipment. The Indian healthcare industry is growing at a tremendous pace due to its strengthening coverage, services, and increasing expenditure by public as well private players. Health care is the fundamental need for humanity. Medical Tourism in India is one of the best options available to people across the globe to undergo treatment with peace of mind. Keywords: Pharma tourism, Medical treatment, Health care, Hospitals and medical tourists.